Analysis Of Factors Related To Inpatient Satisfaction In Anesthesia Department Of Anwar Makkatutu Hospital Bantaeng - Firman, Firman; Zainuddin, Zainuddin; Arfenti Amir (Jurnal EduHealth, 2024)
Patient satisfaction is very important for hospitals to survive. If the hospital can provide good service according to patient expectations, then patients or consumers will certainly return to use the health service. Therefore, the quality of health services is closely related to patient satisfaction received from health services. This study aims to analyze factors related to the satisfaction of inpatients in the anesthesia department at Anwar Makkatutu Bantaeng Hospital. This type of research is quantitative research with a cross-sectional design, the sample in this study was 100 respondents. The sampling method was carried out by purposive sampling. The results of the statistical test analysis used the chi-square test and logistic regression test. Where the results showed that there was a significant relationship with (p <0.05). The technical competence variable with p 0.002 <0.05, for the effectiveness variable p 0.001 <0.05, the interpersonal relationship variable p 0.013 <0.05. From the results of the logistic regression test, effectiveness was obtained (p 0.010; OR Exp (B) = 4.002). The conclusion of this study is that the variables of technical competence, effectiveness, and interpersonal relations have a significant relationship with patient satisfaction. While the dominant variable that influences the satisfaction of inpatients in the anesthesia department at Anwar Makkatutu Bantaeng Hospital is the Effectiveness variable.